2014
DOI: 10.7763/jocet.2014.v2.133
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Distillery Spentwash by Electrocoagulation

Abstract: Abstract-Effluent from distilleries, known as spent wash, leads to extensive soil and water pollution. Removal of pollutants and color from distillery effluent is becoming increasingly important from environmental and aesthetic point of view. Effluent from distilleries contains certain recalcitrant compounds. In the present work effort were made to reduce chemical oxygen demand (COD) from distillery effluent by electrocoagulation. The maximum COD removal efficiency of 98% was obtained at solution pH of 7.2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
0
12
0
1
Order By: Relevance
“…The major conflicts associated with textile industries are high water consumption, dye pigments, toxic metals, bases, acids, toxic compounds, and total dissolved solids (TDS) present in wastewater. [1][2][3] The colored textile wastewater not only prohibits photosynthesis activity, it also increases the gene toxicity, carcinogenic, and mutagenic properties of the water, which are major threats to living species or the environment. [4][5][6] Textile dyes have complex structures, synthetic origin, and are non-biodegradable in nature, which makes it necessary to remove them from industrial effluents before being disposed into various hydrological systems.…”
Section: Introductionmentioning
confidence: 99%
“…The major conflicts associated with textile industries are high water consumption, dye pigments, toxic metals, bases, acids, toxic compounds, and total dissolved solids (TDS) present in wastewater. [1][2][3] The colored textile wastewater not only prohibits photosynthesis activity, it also increases the gene toxicity, carcinogenic, and mutagenic properties of the water, which are major threats to living species or the environment. [4][5][6] Textile dyes have complex structures, synthetic origin, and are non-biodegradable in nature, which makes it necessary to remove them from industrial effluents before being disposed into various hydrological systems.…”
Section: Introductionmentioning
confidence: 99%
“…For pH < 6, reducing the protons to H 2 and producing hydroxide ions in solution caused less COD removal efficiency . Khandegar and Saroh reported that the maximum COD removal efficiency of 84.6 and 76.9% was determined at pH 7.2 for Al‐Al and Fe‐Fe electrodes, respectively . Wang et al also investigated the efficiency of COD removal at different pH values, ranging from 2.5 to 9.5.…”
Section: Resultsmentioning
confidence: 99%
“…[44] Khandegar and Saroh reported that the maximum COD removal efficiency of 84.6 and 76.9% was determined at pH 7.2 for Al-Al and Fe-Fe electrodes, respectively. [45] Wang et al [46] also investigated the efficiency of COD removal at different pH values, ranging from 2.5 to 9.5. The optimal pH of their study was found to be 5.1 and the COD removal efficiency was about 66% using Al-Al electrodes.…”
Section: The Effect Of Ph On Cod Removal Efficiencymentioning
confidence: 99%
“…[8].They used hybrid material composed of waste tyre rubber and zeolite.They observed that increase in the hydraulic retention time(HRT) brought about an improvement in the effluent quality.Kulkarni and Goswami used bagasse flyash as an adsorbent for organic matter removal from wastewater [9]. They carried out investigation in batch and column modes with satisfactory results.Electrocoagulation was used for organic matter removal by Khandegar and Saroh [10].They obtained COD removal efficiency was 84.6 % and 76.9 % at initial pH (7.2).Many investigations have been varried out for COD removal by using various advanced biological treatment [11][12][13][14]. These treatment includes both, aerobic and anaerobic methods.…”
Section: Literature Reviewmentioning
confidence: 99%